A rare case of a patient with PPP syndrome presenting pancreatic pseudocysts, panniculitis, and symptoms of polyarthritis. A radicular cyst of the upper jaw could be another manifestation of the syndrome. Issue 4 (14th January 2020) - Konschake, Wolfgang; Westphal, Thea; Jünger, Michael; Arnold, Andreas; Lutze, Stine
Abstract: In rare cases, pancreatic enzymes can enter the bloodstream and cause fat necrosis in the bone and tissue leading to a disorder called pancreatitis, panniculitis, and polyarthritis syndrome. Clinicians should have this syndrome in mind when treating patients with pancreatitis. Abstract : In rare cases, pancreatic enzymes can enter the bloodstream and cause fat necrosis in the bone and tissue leading to a disorder called pancreatitis, panniculitis, and polyarthritis syndrome. Clinicians should have this syndrome in mind when treating patients with pancreatitis.